Pengembangan Destinasi Pariwisata Kreatif Melalui Pasar Lumpur - Selfi Budi Helpiastuti (Journal of Tourism and Creativity, 2019)
Abstract The development of creative tourism destinations has become a "trend" in the last decade. Starting from a creative idea for an attraction, the addition of activities of the tourists to follow activities presented, to regional imagery at the regional, national and even international, which is mostly done by every region / city. This paper aims to describe the development of creative tourism destinations through the mud market. The author uses discourse analysis approach to analyze the development of creative tourism destinations. In the development of creative tourism destinations, an understanding of 3 (three) components in creative tourism are: (1) something to see, (2) something to do and (3) something to buy. The results of this analysis indicate that in the development of creative tourism destinations using two components only something to see and something to do, by creating attractions and activities of the creative and innovative tourists typical of the area. However, in terms of practical development of creative tourism destinations is balanced with something to buy associated with the development of creative economy as a driver of tourism economy. Keywords: Creative Tourism, Something to See and Something to Do